DESAIN KURSI KULIAH DENGAN METODE BRAINSTORMING DI FAKULTAS TEKNIK UNIVERSITAS QUALITY MEDAN - Darnianti Darnianti; Yusnia Sinambela (Universitas Quality, 2018)
The purpose of designing a lecture chair with additional functions is to provide comfort to students while wearing a lecture chair for a long time, ease in meeting the needs of the students. The lecture chairs are designed to suit the needs of the students, such as comfortable seating, board supplies for writing, bags and there is also a drinking area on the left. as well as for students to not bother holding their bags while writing and listening to lecturers teaching. The technique used in alternative development is through brainstorm. The use of this technique by collecting some input obtained from the students who had sat in the lecture chairs in the Department of Industrial Engineering Faculty of Engineering University of Quality. From the input obtained through brainstorming made a morphological map that is useful to choose the best alternative in designing a versatile lecture product.